Motion and force measurement of human fingertips during manual operation to achieve high-precision assembly by articulated robots. (December 2022) - Yamashita, Takahito; Suzuki, Hikaru; Tasaki, Ryosuke
Abstract: In this paper, a novel high-precision assembly robotic system capable of performing all kinds of tasks without failing is proposed. Specifically, the proposed robot's operation is focused on precision part fitting, which is a difficult task, considering the current technology, and on eliminating "assembly failure" such as biting of shafts and holes. This is achieved by exploiting the feeling of human fingertips during a manual operation performed by a worker. The main objective is to increase the types of tasks that can be performed by the robots. The proposed robotic system is capable of overcoming problems, such as "high installation cost, " "setup difficulties for particular products, " and "inability to automate assembly tasks." In this study, the configuration and validity of an assembly motion analysis system, which measures motion and force information during an assembly task, is reported. After validating the system, it is confirmed that the force information when performing an actual task can be correctly obtained. In addition, these information are used to show the difference between successful and failed fitting tasks.